Navigating Bisexual Identity in Baby Reindeer: A Queer Content and Narrative Analysis. - Hanita, Salsabila Nur; Nirmalawati, Widya (Universitas Pahlawan Tuanku Tambusai, 2025)
Sexual identity is influenced by personal experiences, social norms, and cultural expectations. Although research on LGBTQ+ issues has increased in recent years, stories about bisexual men who have experienced trauma remain limited and underrepresented. This study explores how the Netflix series Baby Reindeer, based on the real-life story of Richard Gadd, presents the complex journey of discovering sexual identity through trauma and emotional struggle. Using qualitative content analysis and narrative analysis guided by queer theory—particularly the ideas of Michel Foucault and Judith Butler—this research focuses on three key episodes to examine how power, identity, and social pressure affect the main character, Donny. The findings reveal that Donny’s struggle illustrates how bisexual identity is shaped by shame, silence, and the need for acceptance. Baby Reindeer offers a meaningful portrayal of queer male experiences and serves as a powerful example of how media can challenge stereotypes and foster deeper understanding of sexual identity.